The Vulnerability of Male Gender and State Response in the Female Labor Protection Policy: A Case Study of New Industrial Communities in Purbalingga Regency - Tobirin Tobirin (Indonesian Association for Public Administration, 2019)
This article discusses the role dominance female gender in the public domain compared to male. So far, gender relations always place female in subordinate conditions and in one condition, male dominate. Minimal gender relations are assessed from the opposite condition. Male is subordinated and female dominate, where male is more vulnerable than female. The purpose of this article is to analyze the vulnerability of male in the labor family in the state's response to female labor protection policies. The research method used is a mixed method, an approach that combines quantitative methods with survey and qualitative approaches with in-depth interviews. The results of this study indicate new gender relations in the family of workers. Female workers become the main breadwinner, gain trust in financial institutions, and develop economic networks through the plasma industry by empowering the surrounding community and accessibility to work. Meanwhile, male is in vulnerable positions with limited employment opportunities, lower income, and feel ashamed of domestic roles. Besides, state response in public policy is less favorable to male in employment; countries in responding to the implications of the emergence of new gender relations still assume female domination in the domestic sphere. In view of this, the local government of Purbalingga Regency should do the following; a) develop family care policies by assuming new female gender roles that are more dominant in the public sphere. b) Build awareness of the advancement of female as a positive thing in realizing a harmonious family by the role of new males who have high gender awareness.